PENGARUH NILAI PERUSAHAAN: STRUKTUR MODAL, UKURAN PERUSAHAAN DAN INVESMENT OPPORTUNITY SET - Yusnita Maulidya Rahmah; Tumirin Tumirin (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Business competition in Indonesia encourages companies to maximize company value through stock prices, which reflect their performance and prospects in the market. The purpose of this study is to determine and analyze the effect of capital structure, firm size and investment opportunity set on firm value. This research approach is based on a quantitative approach. The population and research sample are Banking Company that have positive profits and are listed on the IDX in 2019-2023. The data analysis technique uses multiple linear regression analysis. The results show that capital structure, company size and investment opportunity set have an effect on firm value.